Paediatric minor head injury applied to Paediatric Emergency Care Applied Research Network CT recommendations: An audit - Jacques du Plessis; Sharadini K. Gounden; Carolyn Lewis (South African Journal of Radiology, 2022)
Background: Traumatic brain injury (TBI) is a common cause of paediatric morbidity and mortality, with higher TBI rates in low- and middle-income countries. Non-contrast brain CT is the gold standard for diagnosing intracranial injuries; however, it exposes patients to ionising radiation. The Paediatric Emergency Care Applied Research Network (PECARN) clinical decision rule (CDR) aids clinicians in their decision-making processes whilst deciding whether a patient at very low risk of a clinically important TBI (ciTBI) requires a CT scan.